Population response of intestinal microbiota to acute Vibrio alginolyticus infection in half-smooth tongue sole (Cynoglossus semilaevis) - Hao, Yaotong; Zhao, Yaxian; Zhang, Yitong; Liu, Yufeng; Wang, Guixing; He, Zhongwei; Cao, Wei; Han, Tian; Zhang, Xun; Zhang, Ziying; Wang, Yufen; Gong, Chunguang; et al. (Frontiers in Microbiology, 2023)
Introduction Vibriosis causes enormous economic losses of marine fish. The present study investigated the intestinal microbial response to acute infection of half-smooth tongue sole with different-dose Vibrio alginolyticus within 72 h by metagenomic sequencing. Methods The inoculation amount of V. alginolyticus for the control, low-dose, moderate-dose, and high-dose groups were 0, 8.5 × 101, 8.5 × 104, and 8.5 × 107 cells/g respectively, the infected fish were farmed in an automatic seawater circulation system under a relatively stable temperature, dissolved oxygen and photoperiod, and 3 ~ 6 intestinal samples per group with high-quality DNA assay were used for metagenomics analysis. Results The acute infections with V. alginolyticus at high, medium, and low doses caused the change of different-type leukocytes at 24 h, whereas the joint action of monocytes and neutrophils to cope with the pathogen infection only occurred in the high-dose group at 72 h. The metagenomic results suggest that a high-dose V. alginolyticus infection can significantly alter the intestinal microbiota, decrease the microbial α-diversity, and increase the bacteria from Vibrio and Shewanella, including various potential pathogens at 24 h. High-abundance species of potential pathogens such as V. harveyii, V. parahaemolyticus, V. cholerae, V. vulnificus, and V. scophthalmi exhibited significant positive correlations with V. alginolyticus. The function analysis revealed that the high-dose inflection group could increase the genes closely related to pathogen infection, involved in cell motility, cell wall/ membrane/envelope biogenesis, material transport and metabolism, and the pathways of quorum sensing, biofilm formation, flagellar assembly, bacterial chemotaxis, virulence factors and antibiotic resistances mainly from Vibrios within 72 h. Discussion It indicates that the half-smooth tongue sole is highly likely to be a secondary infection with intestinal potential pathogens, especially species from Vibrio and that the disease could become even more complicated because of the accumulation and transfer of antibiotic-resistance genes in intestinal bacteria during the process of V. alginolyticus intensified infection.